2021
DOI: 10.1088/1361-6668/abe360
|View full text |Cite
|
Sign up to set email alerts
|

Dense rotational twins in superconducting (111)-orientated δ-NbN epitaxial films on 4H-SiC substrates

Abstract: In order to confirm the superconductivity observed in hexagonal ϵ-NbN reported recently, we have deposited NbN film on (0001) 4H-SiC substrate, with good lattice match, intentionally to grow hexagonal NbN phase. The detailed structural analysis show that the deposited films are (111)-orientated δ-NbN phase with dense rotational (60°) twins. Double diffraction effect in selected area electron diffraction and Moiré fringes in high resolution transmission electron microscope images confirm the existence of rotati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 59 publications
1
6
1
Order By: Relevance
“…The interplanar distance value (2.55 Å) was consistent with the value (2.558 Å) from the XRD result of the 15 nm thick film. The result confirmed that the growth model is the same as previously mentioned and in the [20,26,30]. NbN atoms are periodically well-ordered with (111) planes parallel to (001) planes of the Z-cut LN substrates.…”
Section: Crystal Structures Of Nbn Thin Films On Ln Substratessupporting
confidence: 86%
See 4 more Smart Citations
“…The interplanar distance value (2.55 Å) was consistent with the value (2.558 Å) from the XRD result of the 15 nm thick film. The result confirmed that the growth model is the same as previously mentioned and in the [20,26,30]. NbN atoms are periodically well-ordered with (111) planes parallel to (001) planes of the Z-cut LN substrates.…”
Section: Crystal Structures Of Nbn Thin Films On Ln Substratessupporting
confidence: 86%
“…Due to the thinness of films and the HRXRD method, the peak intensity is low. Only the (111) peaks of NbN were clearly observed, same as those in [20,26,30,31]. Besides, thickness of the ultrathin films limits the grain size, resulting in a large full width half maximum value of the XRD peaks [32].…”
Section: Crystal Structures Of Nbn Thin Films On Ln Substratesmentioning
confidence: 74%
See 3 more Smart Citations